A new coastal species of Pseuderanthemum (Acanthaceae) from Loyalty Islands (New Caledonia) and Vanuatu with notes on P. carruthersii - Gâteblé, Gildas (PhytoKeys, 2019)
Abstract. When dealing with the taxonomy of Pacific coastal species within the region of New Caledonia and Vanuatu, one should examine all names published in Australasia and other Pacific islands. When the putative new species is also closely related to a highly praised ornamental species with many cultigens and with many old horticultural names, the task becomes more arduous. This is the case for the new species we describe as Pseuderanthemum melanesicum Gâteblé, Ramon & Butaud, which is closely related to the now pantropical cultivated species P. carruthersii (Seem.) Guillaumin s.l. Compared to P. carruthersii, P. melanesicum has carnose and shiny leaves, pedicels and sepals covered with glandular hairs, a short and enlarged corolla tube and can produce fertile capsules. The new species is a coastal taxon occurring naturally in the Melanesian archipelagos of New Caledonia and Vanuatu. This species seems uncommon in the Loyalty Islands but more common in the archipelago of Vanuatu and we propose it as Critically Endangered in New Caledonia, Vulnerable in Vanuatu and Least Concern when the IUCN evaluation is done globally.